PEMBELAJARAN PADA MIN MESJID RAYA BAITURRAHMAN BANDA ACEH - Rika Dewi, Cut Zahri Harun, Sakdiah Ibrahim. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstraction: The teacher performance is the result of works done by a teacher, both in quality and quantity in implementing tasks in accordance with his or her responsibilities and authorities based on work standards that have been set. The objective of this research was to determine the ability and accuracy, quality, initiative, and obstacles faced by the teachers in improving the learning process at Islamic Elementary School (MIN) of Mesjid Raya Baiturrahman of Banda Aceh. This research qualitative approach. The techniques of data collection used in this research were interview, observation, and documentation. The research subjects were the principal, teachers, and students. The results of the research showed that: 1) the ability of teachers in preparing Lesson Plan already available, as shown when the teachers did not feel confused and have difficulties any longer because all teaching materials had been prepared in accordance with the competence formulated clearly and concretely. However, the learning process had not been entirely successful because some teachers had not used correctly the lesson Plan; 2) the quality and initiative of the teachers in the learning process shown was still not good such as the Lesson Plans made by the teachers had not been meet the quality standards, furthermore the teachers lack the skills to ask open-ended questions, but closed-ended question that had been given frequently to the students, this was because the lack of mastery of broader teaching materials. This condition made some students difficult to develop their critical thinking, imagination and deep analysis in learning, thus it was viewed from the improvement of students’ learning achievement has not improved significantly because all teachers were just preparing all the demands of the learning process; and 3) the obstacles found by the principal in improving the teachers’ performance were: lack of the availability of funds to train the teachers at out of hours of work, still have few teachers who were less active and the result of the training which did not influence the colleagues, thus this condition affected the improvement of the teachers’ performance in carrying out the learning.Keywords: The Performance of Teacher, Learning Process, and MIN Mesjid RayaAbstak: Kinerja guru dalam proses pembelajaran adalah hasil kerja seorang guru, baik secara kualitas maupun kuantitas dalam melaksanakan tugas sesuai dengan tanggung jawab dan wewenangnya berdasarkan standar kinerja yang telah ditetapkan. Tujuan penelitian adalah untuk mengetahui: kemampuan dan ketepatan, kualitas, inisiatif,  dan kendala guru dalam meningkatkan proses pembelajaran pada MIN Mesjid Raya Baiturrahman Banda Aceh. Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Subjek dalam penelitian ini adalah Kepala Sekolah, Guru, dan Siswa. Hasil penelitian menunjukkan bahwa: 1) Kemampuan guru-guru dalam membuat RPP di sekolah sudah ada, sebagaimana terlihat saat melakukan proses pembelajaran guru merasa tidak bingung dan kesulitan lagi, karena semua bahan ajar sudah disiapkan, sesuai dengan kompetensi yang dirumuskan secara jelas dan konkrit. Namun demikian, proses pembelajaran belum sepenuhnya sukses, karena masih ada sebahagian guru yang belum tepat menggunakan RPP pada saat proses pembelajaran berlangsung; (2) Kualitas dan inisiatif guru dalam proses pembelajaran terlihat masih masih belum baik, seperti Rencana Pelaksanaa Pembelajaran (RPP) yang dibuat oleh guru belum semuanya berkualitas, kemudian guru kurang memiliki keterampilan bertanya dengan pertanyaan terbuka terhadap siswa, dimana pertanyaan yang sering diberikan guru adalah pertanyaan tertutup, karena kurangnya menguasai bahan ajar yang lebih luas. Kondisi ini membuat sebahagian siswa kurang dapat mengembangkan daya pikir, imajinasi dan analisis yang tinggi dalam belajar, sehingga dilihat dari peningkatan prestasi belajar siswa belum mengalami peningkatan yang signifikan, karena guru hanya mempersiapkan semua tuntutan proses pembelajaran; dan (3) Kendala yang ditemui kepala sekolah dalam meningkatkan kinerja guru antara lain: kurang tersedianya dana untuk pelatihan guru di luar jam dinas, masih ada sebagian kecil guru kurang aktif dan hasil penataran belum mampu mengimbas kepada temannya, guru juga masih kurang dalam penguasaan landasan kependidikan, sehingga hal ini berdampak terhadap peningkatan kinerja dalam melaksanakan pembelajaran.Kata Kunci: Kinerja Guru, Proses Pembelajaran, dan MIN Mesjid Raya